INQUIRY UNTUK MENINGKATKAN KREATIVITAS SISWA PADA MUATAN PELAJARAN IPS KELAS IV MADRASAH IBTIDAIYAH NW DASAN AGUNG - Taufik, Amalia; Tahrid, Tahrid (Universitas Muhammadiyah Mataram, 2023)
This study aims to increase student creativity through the Inquiry Learning Model in social studies class IV content at MI NW Dasan Agung. The type of research used was classroom action research (CAR), which was conducted in 2 cycles, each cycle consisting of 2 meetings and going through several stages such as: planning stage, acting stage, observation stage and reflection (reflecting). while data collection techniques use Observation Sheets, Questionnaires, and Documentation. The results of this study indicate that the use of the Inquiry Learning Model can increase student creativity. This can be seen from the results of the questionnaire data obtained by students, the creativity of students using the Inquiry Learning Model has increased from cycle I to cycle II, in cycle I the percentage obtained reached 47.26%, while after making improvements in cycle II, then the percentage obtained was 89.9% in the very good category. So that it is clear that the application of the Inquiry Learning Model in social studies content can increase the creativity of class IV MI NW Dasan Agung Mataram City.